From Transactional Fundraising to Systemic Governance of Donor Capital and Donor Experience - Tov Baazov , Siman (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
With aggregate fundraising amounts steady, institutional philanthropy faces a growing risk of donor loss, revenue instability and concentration. These issues underscore the ever-increasing significance of governance systems that can maintain donor relationship in the long run as opposed to the use of transactional fundraising models. The paper uses an analytical approach that is grounded in a governance-based analysis using secondary longitudinal data of 27 nonprofit organizations in the United States, United Kingdom, and Germany between 2020 and 2024. The effects of governance-based donor management were examined through comparing the rates of donor retention, indicators of lifecycle transition, measures of revenue stability, and the measures of donor concentration. The results prove that governance redesign is related to dramatic changes in the stability of donors and financial predictability. The average annual retention of the donors rose by 41.2 to 68.5 and the number of recurring donors changed 26.7 to 54.3. The revenue deviation between years decreased to 15.4% since the value had decreased by 39.1%.